2020
DOI: 10.1108/aeat-12-2019-0266
|View full text |Cite
|
Sign up to set email alerts
|

Robust error-based active disturbance rejection control of a quadrotor

Abstract: Purpose The control of a quadrotor unmanned aerial vehicle (UAV) is a challenging problem because of its highly nonlinear dynamics, under-actuated nature and strong cross-couplings. To solve this problem, this paper aims to propose a robust control strategy, based on a concept of active disturbance rejection control (ADRC). Design/methodology/approach The altitude/attitude dynamics of a quadrotor is reformulated into the ADRC framework. Three distinct variations of the error-based ADRC algorithms, with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Remark 7. The presence of control signal u(t) in the total disturbance d(•), visible in (7), does not cause instability of the system as long as condition (5) is satisfied.…”
Section: Overview Of Implemented Adrc Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Remark 7. The presence of control signal u(t) in the total disturbance d(•), visible in (7), does not cause instability of the system as long as condition (5) is satisfied.…”
Section: Overview Of Implemented Adrc Algorithmmentioning
confidence: 99%
“…It is, however, recommended to be as precise as possible when setting the value b(•). Not only it can lead to the system instability when set outside the aforementioned acceptable range, but also can cause the total disturbance to be harder to estimate, since the difference between the real input gain parameter b(•) and its assumed value b(•) is incorporated within the total disturbance, represented by (7). Furthermore, when the value b(•) approaches the boundaries of ( 5), it may cause some unwanted oscillations in the system behavior.…”
Section: Estimate Of Input Gain B(•)mentioning
confidence: 99%
See 1 more Smart Citation
“…The error-based ADRC has been successfully applied by now to a variety of control problems including mechanical vibration compensation [21,22], robotic manipulator control [23,24], observer design with suppression of sensor noise [25][26][27], position control of a telescope mount [28], UAV control [29,30], as well as power electronics control [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focus on the stability and performances of ADRC for multirotor UAVs when parametric uncertainties are not neglected. ADRC has already been successfully applied for the control of this kind of aerial vehicles, mostly on the attitude control loop like in Castillo et al (2016), Yang et al (2018), Yuan et al (2019) and Castillo et al (2019) or attitude and altitude as in Lechekhab et al (2020), but also for both position and attitude control like in Zhang et al (2018) and Xu et al (2020). It was demonstrated that the uncertainties on model parameters (the uncertainties of mass, inertia and actuation efficiency) can be considered as additional disturbances to be estimated by the observer and that they do not affect the stability under some conditions (existence of upper bounds).…”
mentioning
confidence: 99%